2020
DOI: 10.9734/jerr/2020/v12i317083
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Impact of Open Burning of Municipal Solid Wastes Dumps in Parts of Jos Metropolis, Nigeria

Abstract: Refuse dumpsites are found scattered within and outside cities in Nigeria and the open burning of these dumps is a common practice mainly as a waste and odour reduction measure. Open incineration of wastes emits dangerous gases into the atmosphere. The environmental and public health hazards related to open burning of wastes dumps have often been overlooked in most parts of Nigeria and there is limited documentation on this for the study area. This study is aimed at investigating the environmental effect of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…The results of the practice prove that the presence of open dumps contributes to the increase in air pollution measured around landfills. They showed that in the vicinity of the landfill, oxygen levels in the vicinity were below a comfortable level of 19.5% (Daffi et. al., 2020).…”
Section: Waste Collectionmentioning
confidence: 99%
“…The results of the practice prove that the presence of open dumps contributes to the increase in air pollution measured around landfills. They showed that in the vicinity of the landfill, oxygen levels in the vicinity were below a comfortable level of 19.5% (Daffi et. al., 2020).…”
Section: Waste Collectionmentioning
confidence: 99%
“…The exact quantity wastes burnt annually in the study area is not known but numerous evidences point to open burning as the predominant means of disposal of solid wastes in Nigeria [7,13,14,18,30,[35][36][37]. According to a study conducted in Benin City by Ezeudu and Ezeudu [38]…”
Section: Estimation Of Emission Rates Of the Pollutantsmentioning
confidence: 99%
“…The studies on the extent and compositions of municipal wastes in Nigeria have been reported by several authors [12,14]. A few studies on anthropogenic air pollutants from combustion of municipal solid wastes in Nigeria also exist in the literature [2,15,18]. However, the studies by these authors were limited in scope based on the number of pollutants and study areas covered.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, there are incident reports confirming the impacts of waste on the local community. In 2015, in the Qoaling township, a toy from a dumpsite exploded injuring children, and in another incident in Lithabaneng township, medical waste mixed with commercial and industrial waste were found [ 9 ]. The impacts of solid waste management on the health of communities are not well understood and often perceived as an aesthetic problem rather than a public health problem but studies have confirmed public health risks throughout the waste cycle from generation to final disposal [ 10 ].…”
Section: Introductionmentioning
confidence: 99%